Local Wisdom-Based Digital Marketing Strategy in Brambang Gareng Slawe MSMEs - Toto Heru Dwihandoko (LPPM Institut Pendidikan Nusantara Global, 2025)
This study examines the implementation of local wisdom-based digital marketing strategies by Brambang Gareng Slawe MSMEs in adapting to the demands of the digital market. Rooted in a qualitative case study approach, the research was conducted in Slawe Village, Mojokerto Regency, East Java, with seven purposively selected informants. Data were collected through in-depth interviews, participant observation, and documentation, and analysed thematically. The findings reveal that while MSMEs in this region have begun to engage digital platforms such as WhatsApp, Facebook, and Instagram, their digital marketing strategies remain intuitive and unstructured. The integration of local values, such as traditional recipes, Javanese expressions, and visual cultural symbols, has enhanced product authenticity and emotional connection with consumers. However, significant barriers persist, particularly the lack of digital literacy, limited access to infrastructure, and the absence of dedicated branding personnel. Despite these constraints, the rise in digital consumer behaviour and community-based platforms presents strategic opportunities. This study concludes that cultural branding, when combined with basic digital marketing literacy, offers a viable pathway for rural MSMEs to achieve sustainable competitive advantage in the digital economy.